"We Are All Convicted Criminals"? Prisoners, Protest and Penal Politics in the Republic of Ireland. Issue 2 (17th April 2017) - Behan, Cormac
Abstract: This article examines protests by "ordinary" prisoners in the Republic of Ireland, which began in the 1970s. Whereas "political" prisoners have attracted significant academic and popular attention, little historical research exists about organizations that represented "ordinary" prisoners, such as the Prisoners Union. Yet "ordinary" prisoners demonstrated that they too had the capacity to organize. Though their protests took similar forms, the state adopted a markedly different approach when dealing with the two groups of prisoners. Despite appalling prison conditions, governments rejected the Prisoners Union's claim to represent "ordinary" prisoners and resisted its demands for penal reform. In contrast, after more prolonged protests, and despite assertions that the paramilitary organizations to which "political" prisoners belonged posed an existential threat to the state, the government neutralized their protests by accepting their representation, improving their conditions, and effectively recognizing them as a special category of prisoner.